2018
DOI: 10.1002/ps.5247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold storage on the quality ofTrichogramma dendrolimiMatsumura (Hymenoptera: Trichogrammatidae) reared on artificial medium

Abstract: BACKGROUND: Trichogramma dendrolimi Matsumura is an important egg parasitoid that can be used in the biological control of lepidopteran pests. The effects of storage temperature, developmental stage and storage duration on development and survival were investigated to determine the optimum storage conditions for rearing T. dendrolimi in vitro. RESULTS: The three investigated factors significantly impacted all the biological parameters except for parental G1 and offspringG2 sex ratios. The responses of in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This is consistent with the study on B. oleae, which found that adults subjected to pupal cold storage made fewer oviposition holes on olives than the controls, and the number of progeny from the pupae developed from these olives were also fewer than the controls [23]. Research on Trichogramma dendrolimi (Matsumura) (Hymenoptera: Trichogrammatidae) has also shown that the lifetime reproduction of parasitoids after pupal cold storage was notably lower than that of control, regardless of the cold-storage treatment [49].…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the study on B. oleae, which found that adults subjected to pupal cold storage made fewer oviposition holes on olives than the controls, and the number of progeny from the pupae developed from these olives were also fewer than the controls [23]. Research on Trichogramma dendrolimi (Matsumura) (Hymenoptera: Trichogrammatidae) has also shown that the lifetime reproduction of parasitoids after pupal cold storage was notably lower than that of control, regardless of the cold-storage treatment [49].…”
Section: Discussionsupporting
confidence: 86%
“…However, keeping parasitoids at a sub-ambient temperature can result in cold injuries and excessive consumption of energy reserves, resulting in undesirable effects on the quality and quantity of post-storage parasitoids [ 11 ]. Hence, to minimize losses in the performance of parasitoids after undergoing storage, packaging, and shipment, recent research has focused on optimizing the tradeoffs between quality and the cold storage protocol [ 12 , 13 , 14 ]. For braconid parasitoids against tephritid pests, the impacts of cold storage have been evaluated in several species, such as Psyttalia humilis (Silvestri), Psyttalia ponerophaga (Silvestri), Fopius arisanus (Sonan), and Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae); these works have provided a lot of valuable information for facilitating the practical application of biological control programs [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characteristics, including trehalose content and trehalase activity in T. dendrolimi, continuously reared on artificial medium (in vitro) versus those reared on A. pernyi eggs (in vivo), were also studied [11]. The quality of in vitro reared T. dendrolimi was strongly affected by cold storage, but prepupae could be successfully stored at 13 • C for up to 4 weeks [12].…”
Section: Introductionmentioning
confidence: 99%
“…Trichogramma spp. show different reactions to low temperatures when reared on different hosts or media [12,13]. For T. dendrolimi, the developmental threshold temperature was different among geographical populations and hosts: 10.34 • C for south population reared on Philosamia cynthia ricini [13]; 10.1 • C for the south population reared on C. cephalonica [14]; 5.34 • C/5.1 • C, 5.82 • C/5.42 • C, 11.03 • C/14.83 • C, and 12.37 • C/11.58 • C for the north population (egg, larva, prepupa and pupa) reared on A. pernyi [15,16].…”
Section: Introductionmentioning
confidence: 99%